Leading Lean Six Sigma : research on leadership for operational excellence deployment. - Laureani, Alessandro (Emerald points., 2021)
Leading Lean Six Sigma: Research on Leadership for Operational Excellence Deploymentassesses the impact of organizational leadership on the deployment of Lean Six Sigma in organisations. This book details what leadership traits are needed for a successful deployment, presenting a ground-breaking leadership dependency model.